Economic evaluation of five years aged mango-based agroforestry practices established in the deforested land in the Madhupur Sal forest of Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
The study was carried out from July 2018 to June 2019 to analyze the economic profitability of mango-based agroforestry practices established in the deforested land in the Madhupur Sal forest. A sample of 5 years old established promising five Mango-based agroforestry practices viz. Mango- Pineapple-Ginger-Papaya-Banana-Turmeric, Mango-Pineapple-Ginger-Papaya-Banana, Mango- Turmeric-Papaya-Aroid, Mango-Lemon-Turmeric and Mango-Pineapple along with a nonagroforestry combination (except mango tree) for each of the respective practices having 0.12 ha plot area were selected through literature review, practical observation and consult with the community. A total of 100 farmers in which 10 for each of the respective combinations were selected for collecting required data. In order to evaluate the economic performances, data related to tree and crop parameters were collected from the respective plots as well as individual farmers in order to calculate the incurred cost, gross return, net profit, benefit-cost ratio (BCR) and land equivalent ratio (LER). The results revealed that the total calculated gross return (Tk/ha) and net profit (Tk/ha) for five years of the selected Mango-based agroforestry practices were 1076344, 956095, 816520, 443633, 253686 and 688925, 584723, 467892, 162817, 7998 respectively. While the total gross return (Tk/ha) and net profit (Tk/ha) for five years of the selected non-agroforestry combinations were 622886, 503430, 298289, 283782, 185968 and 356742, 248505, 89955, 89299, 5468 respectively. Among them the highest (1076344 Tk/ha and 688925 Tk/ha) gross return and net profit incurred for Mango-Pineapple- Ginger-Papaya-Banana-Turmeric based agroforestry practice than its non-agroforestry combinations (622886 Tk/ha and 356742 Tk/ha). The BCR and LER of the selected Mango-based agroforestry practices were 2.78, 2.57, 2.34, 1.57, 1.03 and 3.27, 2.76, 2.32, 1.93, 1.37 respectively which indicates, that all the selected Mango-based agroforestry practices were profitable. Therefore, it can be concluded that the economic performance of mango-based agroforestry practice is more profitable than the sole cropping system.J Bangladesh Agril Univ 18(2): 388–394, 2020https://doi.org/10.5455/JBAU.72568